ANALISIS TATANIAGA KOPI ROBUSTA DI KECAMATAN SUMOWONO KABUPATEN SEMARANG - Muhammad Khevin Utama; Wiludjeng Roessali; Wahyu Dyah Prastiwi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2018)
The objectives of the research were 1) Identifying of marketing channels on each marketing institutions 2) Identifiying marketing functions which performed by each marketing institutions 3) Analyzing of marketing margins on each marketing channels 4) Analyzing farmer’s share which performed by each marketing institutions on Sumowono District. The research was conducted in March 2017 until April 2017. The methodology and collecting data was executed through survey, observation, and interview using quetionnaire.The research was held in Sumowono District which the most productive of coffee on Semarang Regency. The location of research were held on 3 villages which were Pledokan’s Village, Ngadikerso’s Village and Kebonagung’s Village, those villages were chosen because that 3 village were guided by Balai Penyuluh Petanian in Sumowono District. The respondents consisted of farmers and traders Robusta coffee. Respondent farmers are 30 respondents which determined by Multistage Sampling. Respondents traders and agent are 15 respondents which determined by Accidental Sampling. The result of research was showed that there are four channels trading system that happened in Sumowono District which are (I) Farmer – Whole Saler – Traders Expoters (II) Farmer – Traders Village – Retail – Consumer (III) Farmer – Traders Village – Whole Saler – Retail – Traders Exporters (IV) Farmer – Traders Village – Whole Saler – Retail – Consumer. Each marketing institutions perform a difference of marketings function.  Marketing’s margin and farmer’s share’s value of the analysis on marketing’s channel I are equal Rp. 5.983,00 and 80,70%, channel II are equal Rp. 6.912,00 and 78%, channel III are equal Rp. 8.918,00 and 74% and channel IV are equal Rp. 10.000,00 and 71%, as well the most efficient marketing channel is channel I. Keyword : farmer’s share; function; coffee; channel; marketing.